The effect of plyometric training on muscular strength and performance level of the Gaza Strip shot put team - ali alakraa, hicham (sports creativity, 2025)
This study aimed to identify the effect of plyometric training on the power and performance level of the Gaza Strip shot put team. The researcher used the experimental method and designed the training program. The study sample consisted of two athletes. The most important results were that the training program achieved good improvement rates, with the improvement rate for the muscular power test reaching 6.49%, and for the performance level, it reached 6.81%.